A highly selective enrichment broth combined with real-time PCR for detection of Staphylococcus aureus in food samples. (August 2018) - Yoon, Ji-Hyeon; Wei, Shuai; Oh, Deog-Hwan
Abstract: A new selective enrichment broth (OSA) was developed for detection of Staphylococcus aureus combined with real-time PCR. Acriflavine, nalidixic acid, potassium tellurite and sodium chloride were added as selective reagents and mannitol, sodium pyruvate, and yeast extract as promoters. The growth of S. aureus (10, 100, 1000 CFU/mL inoculation level) in OSA was superior to that in TSB with 7.5% NaCl (TNaCl). OSA showed a good inhibition ability against 8 strains including 4 Gram-positive and 4 Gram-negative. Further, OSA gave a good recovery of cold-, acid-, and heat-stressed cells comparable to TSBYE but superior to TNaCl. A real-time PCR targeting the nuc gene was developed and the standard curve was established from 9.1 × 10 7 to 9.1 × 10 2  cfu/mL with a high regression coefficient of determination (R 2  = 0.999) and a high amplification efficiency of 96.362%. Using artificially contaminated food samples (kimbap, milk, and spam) with a level of ∼10 CFU/25 g or mL, OSA better supported the growth of S. aureus and all samples were readily detected after 12 h enrichment by real-time PCR. In summary, OSA was demonstrated as a promising selective enrichment broth for detection of S. aureus combined with real-time PCR with a total assay time of 15 h. Highlights: A new selective enrichment broth OSA for S. aureus was developed. The OSA showed a good recovery ability of stressed cells comparable to TSBYE. Growth of S. aureus in OSA was better than TNaCl both in culture and food samples. The standard curve of qPCR showed a high amplification efficiency of 96.362%. S. aureus in food samples could be detected after 12 h in OSA combined with qPCR.